-6=-2(3b+9)-5(4-26)

Simple and best practice solution for -6=-2(3b+9)-5(4-26) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6=-2(3b+9)-5(4-26) equation:


Simplifying
-6 = -2(3b + 9) + -5(4 + -26)

Reorder the terms:
-6 = -2(9 + 3b) + -5(4 + -26)
-6 = (9 * -2 + 3b * -2) + -5(4 + -26)
-6 = (-18 + -6b) + -5(4 + -26)

Combine like terms: 4 + -26 = -22
-6 = -18 + -6b + -5(-22)

Multiply -5 * -22
-6 = -18 + -6b + 110

Reorder the terms:
-6 = -18 + 110 + -6b

Combine like terms: -18 + 110 = 92
-6 = 92 + -6b

Solving
-6 = 92 + -6b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '6b' to each side of the equation.
-6 + 6b = 92 + -6b + 6b

Combine like terms: -6b + 6b = 0
-6 + 6b = 92 + 0
-6 + 6b = 92

Add '6' to each side of the equation.
-6 + 6 + 6b = 92 + 6

Combine like terms: -6 + 6 = 0
0 + 6b = 92 + 6
6b = 92 + 6

Combine like terms: 92 + 6 = 98
6b = 98

Divide each side by '6'.
b = 16.33333333

Simplifying
b = 16.33333333

See similar equations:

| -7(x+2)-11=14+3 | | 12a^2-52ab-40b^2=0 | | 5y+4x-30=180 | | -1.5x-1/4=-6.32 | | 8-8=14x+10x | | X-2y+2z=1 | | W-w+5w+3=8 | | 4x^2+2x=15 | | 7q-6q=14 | | 12n-11n-n+4n+4n=16 | | 10r+r+4r-2r-11r=18 | | 5q-5q+q=11 | | 40x+6(1.5)+4(2x)=855 | | 2x^2+8x-73=-9 | | 6s-5s-s+s=15 | | f(x)=8+3x-x^2 | | 320.05/37 | | 3cosx+14cosx-5=0 | | 3x^2+18x+19=4 | | 4x-5y+3z=-1 | | 9x+4-5x= | | 3(3-5)=18 | | 8(2.416666667+0.6666666667y)+12y+1=30 | | v(x)=(20-2x)(8-2x) | | 18m=30 | | N-14=-6 | | 5/7=10/m | | -6p-4q=10 | | 4y^2+16y+4=0 | | G-g+2g=20 | | 8y+12x+1=30 | | 26i=50 |

Equations solver categories